When will the Covid-19 pandemic peak? - Oliver Linton (Centre for Microdata Methods and Practice (cemmap), 2020)
We carry out some analysis of the daily data on the number of new cases and number of new deaths by (191) countries as reported to the European CDC. We work with a quadratic time trend model applied to the log of new cases for each country. This seems to accurately describe the trajectory of the epidemic in China. We use our model to predict when the peak of the epidemic will arise in terms of new cases or new deaths in other large countires. We find that for the UK, this peak is mostly likely to occur within the next two weeks. The total number of cases per day will peak at around 8000 yielding a little more than 255,000 cases in total.
Keywords: 330; Coronavirus; Epidemie; Trend; Regressionsanalyse; Welt